SOCA Vol. 13 No 3 Desember 2019 - Jurnal Editor (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2019)
abstrak